Squeezing of laser pulses in nonlinear-optical LC cell - Bugaychuk, Svetlana; Iljin, Andrey (Photonics Letters of Poland, 2018)
Controllable compression of the temporal duration of light pulses takes place in a liquid crystal medium via self-action processes of beam mixing, namely, a dynamic Bragg grating formation by incoming light waves with their consequent self-diffraction on the same recorded grating. Wherein, the laser pulse duration should be comparable with the time relaxation constant of the medium while the extent of the temporal compression is controlled by the variation of the input pulse durations and the value of nonlocal response. Full Text: PDF References U. Bortolozzo, S. Residori and J. P. Huignard, "Beam coupling in photorefractive liquid crystal light valves", J. Phys. D: Appl. Phys. 41, 224007 (2008). CrossRef P. Guner and J.P. Huignard, Photorefractive Matrials and their Applications, 1, 2, and 3 (New York Springer) and references therein (2006). CrossRef S. Bugaychuk and E. Tobisch, "Single evolution equation in a light-matter pairing system", J. Phys. A: Math. Theor., 51 (12), 125201 (2018). CrossRef S. Bugaychuk and R. Conte, "Nonlinear amplification of coherent waves in media with soliton-type refractive index pattern", Phys. Rev. E 86, 026603 (2012). CrossRef A. Iljin, "Light-induced order modification – The way to speed up", Journal of Molecular Liquids 267, 38 (2018). CrossRef A. Iljin, "Transient Modulation of Order Parameter and Optical Non-Linearity in a Chiral Nematic Liquid Crystal", Mol. Cryst. Liq. Cryst. 543, 143 (2011). CrossRef D. Wei, A. Iljin, Z. Cai, S. Residori, and U. Bortolozzo, "Two-wave mixing in chiral dye-doped nematic liquid crystals", Opt. Lett. 37, 734 (2012). CrossRef S. Bugayhuk, A. Iljin, O. Lytvynenko, L. Tarakhan and L. Karachevtseva, Nanoscale Res. Lett., 12, 449 (2017). CrossRef